Decisive rule experimental studies to detect objects on the background of the earth surface using polarization differences of radar signals - Burdanova, Ekaterina V.; Zhilyakov, Evgeniy G.; Oleynik, Ivan I.; Mamatov, Aleksandr V.; Nemtsev, Aleksandr N. (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
The task of stationary and moving object detection against the background of the underlying surface (earth) by radar means becomes relevant. A decision rule is being developed to detect objects against the background of the earth surface using the polarization differences reflected from the earth and the objects of radar signals, represented as a measurement vector. Methods: They carry out the experimental studies of the decision function using the data of a full-scale experiment with radar sensing of a piece of land with various objects on it. They provide the numerical values of the information sign obtained estimates used in the decision rules and decision making quality indicators. Results: Experimental studies have shown that the developed decision rule allows detecting inhomogeneities (objects) on the earth surface with a correct detection probability of 0.95%, with the first-type probability of 10-4. Conclusion: The experimental studies, using field data, confirm the high quality indicators of the developed decision rule.